Risk identification and improvement strategies for BMI and physical fitness and health grade cross-classification: a cross-sectional study based on Chinese college students - Guo, Hao (Frontiers in Public Health, 2025)
IntroductionThe decline in physical fitness among university students has become a global concern. Traditional single-metric evaluation methods, such as body mass index (BMI) alone, cannot comprehensively capture students’ health status. This study aimed to establish a BMI–Physical Fitness and Health (PFAH) cross-classification framework to identify distinct risk groups and their characteristics, providing evidence for targeted intervention strategies.MethodsA cross-sectional study was conducted among 3,026 Chinese college students (1,435 males, 1,591 females; aged 18–22 years) assessed using the National Student Physical Fitness and Health Standard. Participants were cross-classified into eight groups according to BMI categories (normal, overweight, obese) and PFAH levels (good, pass, fail). Heat maps, radar charts, and receiver operating characteristic (ROC) curve analyses were used to visualize group features and identify key predictive indicators.ResultsThe most prevalent group was normal-pass (52.1%), followed by normal-good (22.2%) and overweight-pass (11.6%). High-risk groups—obesity-pass, normal-fail, overweight-fail, and obesity-fail—accounted for 3.0%, 4.7%, 2.5%, and 3.0% of the sample, respectively. Each high-risk group exhibited distinct fitness deficiencies: the obesity-pass group had significantly elevated BMI (z = 2.45); the normal-fail group showed poor speed (50 m: z = 0.69); the overweight-fail group displayed reduced flexibility (sit-and-reach: z = –0.47) and muscular endurance (sit-ups: z = –0.45); and the obesity-fail group performed worst in cardiopulmonary endurance (1,000 m: z = 1.60; 800 m: z = 2.30) and muscular strength (pull-ups: z = –0.86). BMI, endurance (1,000 m/800 m), and speed (50 m) were the strongest predictors for identifying high-risk males (AUC = 0.902, 0.801, 0.792) and females (AUC = 0.895, 0.874, 0.731).DiscussionThe BMI–PFAH cross-classification framework effectively distinguishes diverse risk profiles among university students, revealing hidden risk populations (normal BMI but failing fitness) that traditional BMI-based assessments might overlook. Based on these findings, targeted interventions should include weight management while maintaining fitness for the obesity-pass group, anaerobic and speed training for the normal-fail group, and comprehensive improvements in cardiopulmonary function, muscular strength, and flexibility for overweight/obesity-fail groups. This framework provides a practical basis for developing evidence-based health education and personalized intervention strategies in higher education settings.